Răspunsuri

2014-07-31T19:53:59+03:00
√8=2√2
√18=3√2

3(2√2-5x)-2(3x√2 -4)= 2x-6√2 -8x-10

6√2 -15x -6x√2+8= -6x -6√2 -10

-15x -6x√2 +6x = -6√2 -10 -8 -6√2

-9x -6x√2 = -12√2 -18 |:(-3)

3x +2x√2 = 4√2 +6

3x=6  =>x=2

2x√2= 4√2

2x=4  =>x=2
cu placere ;)
Dar, n-am inteles de unde vine :3 :)
impartim toata ecuatia cu (-3)
Gata, am inteles, mersi. :)
;) n-ai pentru ce ;)
2014-07-31T21:08:33+03:00
3(√8-5x)-2(x√18-4)=2(x-3√2)-2(4x+5)
3(2√2 - 5x) - 2(3x√2 - 4) = 2(x - 3√2) - 2(4x + 5)
6√2 - 15x - 6x√2 + 8 = 2x - 6√2 - 8x - 10
-9x - 6x√2 = -18 - 12√2    l * (-1)

9x + 6x√2 = 18 + 12√2
3x(3 + 2√2) = 6(3 + 2√2)

x= \frac{6(3 + 2 \sqrt{2})}{3(3 + 2 \sqrt{2})} =  \frac{6}{3}=2

x = 2